Corelation Between watching movie and speaking skill - Billy Ramadhan Matondang (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The problem of the study in this research was formulated of the research question (1) is there any correlation between the students’ watching English movies in their English speaking skill on third semester of Faculty of Teaching Training and Education of University of Islam Malang. The objective of the research was to help the researcher find out whether there is any correlation between the students’ watching English movies in their speaking on third semester of Faculty of Teaching Training and Education of University of Islam Malang. The research methodology in this research was descriptive correlation in quantitative which consisted of two instruments in collecting the data. The instruments were questionnaire and documentation of speaking score. This research was done at third semester of Faculty of Teaching Training and Education of University of Islam Malang with the total sample is 30 students. The researcher found the result of correlation value r = 0.872 and r-table = 0.361 in the level significance 5% (0.05). The value of correlation product moment stated that r is higher than r-table or (0.872 > 0.361). Therefore, the alternative hypothesis stated that H0 was rejected and H1 was accepted. Based on the table interpretation of number correlation 0.70-0.90 it is clearly stated that there was correlation and the correlation of both variables are high. Because the r (0.872) is between 0.70-0.90 on the table of interpretation. Consequently, it can be concluded that there was a significant correlation between watching English movies and students’ English speaking skill.